The association between anxiety and cardiac interoceptive accuracy: A systematic review and meta-analysis. (September 2022) - Adams, Kiera Louise; Edwards, Alexandra; Peart, Charlotte; Ellett, Lyn; Mendes, Inês; Bird, Geoffrey; Murphy, Jennifer
Abstract: Anxiety is often conceptualised as the prototypical disorder of interoception (one's perception of bodily states). Whilst theoretical models predict an association between interoceptive accuracy and anxiety, empirical work has produced mixed results. This manuscript presents a pre-registered systematic review (https://osf.io/2h5xz) and meta-analysis of 55 studies, obtained via a Pubmed search on 9th November 2020, examining the relationship between state and trait anxiety and objectively measured cardiac interoceptive accuracy as assessed by heartbeat counting and discrimination tasks. Potential moderators of this relationship - the age, gender and clinical diagnoses of participants, the anxiety measures used and the study design - were also explored. Overall, we found no evidence for an association between cardiac interoceptive accuracy and anxiety, with none of the factors examined moderating this finding. We discuss the implications these findings have for future research, with a particular focus on the need for further investigation of the relationship between anxiety and other facets of interoception. Highlights: Anxiety is often linked to cardiac interoceptive accuracy, but results are mixed. This meta-analysis sought to elucidate the presence and direction of associations. No relationship was observed between anxiety and cardiac interoceptive accuracy. This was consistent across different interoceptive accuracy tasks and anxiety measures. No theoretically selected factors were found to moderate this effect.